工業デザイナーの技術開発への寄与とその要因 - 吉岡（小林）, 徹 (Transactions of the Academic Association for Organizational Science, 2016)
Technology development has been regarded as an exclusive field for engineers and scientists. However, the latest case study discovered that industrial designers can contribute even in natural science research. In addition to that, linking cognitive study on inventing process and nature of industrial designing, there is one common theoretical ground, which can bring qualified technologies. In this paper, we test the link between an enrollment of industrial designers in inventing activities and their impacts on inventing outcomes using patent applications to Japan Patent Office from a Japanese electronics manufacturer. By connecting each inventor’s individual affiliation information collected from the design patent, we constructed 75,932 invention-level data points for inventor affiliations to use in our regression analysis. Our analysis reveals a significant contribution by industrial designers to high-impact inventions. Our estimation result shows that an enrollment of industrial designers increases forward citations of a focal patent application by an average of 11%, and at the same time, it causes a delay of growth in forward citations. On the other hand, the theoretical common ground has no significant impact. We can interpret that these contributions of industrial designers come from their latent demand-oriented thinking, which concurs with recent design studies. This study provides a theoretical linkage between industrial designers and technology development.